Mechatronics Systems - Ladislav Jurisica (Communications - Scientific letters of the University of Zilina, 2007)
The term mechatronics refers to systems with special characteristics that can be achieved only as a whole, and cannot be realized through other means. Integrating mechanical and electronic components with control systems and informatics during design was introduced due to new performance requirements on system quality, its overall reliability, dynamics, low energy consumption, low weight, etc. The paper is focused on the basic information about mechatronics.